2016
DOI: 10.1038/srep28178
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to abnormal glucose levels alters drug metabolism pathways and insulin sensitivity in primary human hepatocytes

Abstract: Hyperglycemia in type 2 diabetes mellitus has been linked to non-alcoholic fatty liver disease, which can progress to inflammation, fibrosis/cirrhosis, and hepatocellular carcinoma. Understanding how chronic hyperglycemia affects primary human hepatocytes (PHHs) can facilitate the development of therapeutics for these diseases. Conversely, elucidating the effects of hypoglycemia on PHHs may provide insights into how the liver adapts to fasting, adverse diabetes drug reactions, and cancer. In contrast to declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 54 publications
3
54
1
Order By: Relevance
“…In our current study, however, we consistently observed upregulation of PXR and CYP3A4 in high-glucose conditions and showed that the pharmacologic activation of AMPK robustly repressed glucose-induced PXR transcriptional activity. The discrepancy between our observations and those of Davidson et al 59. could be due to the differences in the experimental systems or cell types used (HepG2 cancer cells vs. primary hepatocytes).…”
Section: Discussioncontrasting
confidence: 99%
“…In our current study, however, we consistently observed upregulation of PXR and CYP3A4 in high-glucose conditions and showed that the pharmacologic activation of AMPK robustly repressed glucose-induced PXR transcriptional activity. The discrepancy between our observations and those of Davidson et al 59. could be due to the differences in the experimental systems or cell types used (HepG2 cancer cells vs. primary hepatocytes).…”
Section: Discussioncontrasting
confidence: 99%
“…Significantly higher (almost double) levels of hepatic cytochrome P450, family 2, subfamily C, polypeptide 19 (CYP2C19) were found in patients in the high‐HIS group compared to the low‐HIS group (http://onlinelibrary.wiley.com/doi/10.1002/hep4.1077/suppinfo). The enzymatic activity and expression level of CYP2C19 protein were reported to decrease with progression of NAFLD, and the expression level of its gene is reportedly influenced by the glycemic state . Further studies are needed to determine the therapeutic potential of CYP2C19 in NAFLD‐associated hepatic insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The enzymatic activity and expression level of CYP2C19 protein were reported to decrease with progression of NAFLD, (51) and the expression level of its gene is reportedly influenced by the glycemic state. (52) Further studies are needed to determine the therapeutic potential of CYP2C19 in NAFLDassociated hepatic insulin resistance. Gene ontology analysis showed down-regulation of mRNA expression of genes involved in the oxidation-reduction process and inflammatory response in the high-HIS group ( Supporting Table S2), which may associate with the lower lobular inflammation score as assessed by liver histopathologic examination (P 5 0.06; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Khetani and Bhatia have demonstrated that 3T3‐J2 fibroblasts induce high levels of functions in PHHs, which is likely due to the ability of the 3T3‐J2 fibroblasts to express diverse hepatocyte‐supportive molecules present in the liver, such as decorin and T‐cadherin . Furthermore, the use of 3T3‐J2 fibroblasts in co‐culture with PHHs does not prevent the effective use of the stabilized PHHs for many applications in drug development (drug toxicity assessment, and hepatitis B/C viral infections) . Therefore, here we created co‐cultures of PHHs and 3T3‐J2 fibroblasts on heparin‐terminated and fibronectin‐coated PEMs and compared the long‐term morphology and functions to those obtained on fibronectin‐coated TCPS (conventional methodology).…”
Section: Discussionmentioning
confidence: 99%